DESAIN PROGRAM PEMBELAJARAN BAHASA INGGRIS SEBAGAI MATA PELAJARAN KEJURUAN PADA KURIKULUM MERDEKA: CONTOH APLIKASI PADA KONSENTRASI KEAHLIAN ANIMASI - Rin Surtantini (BBPPMPV Seni dan Budaya Yogyakarta, 2023)
The current article is a response toward the significance of analysis which brings about theapplicable scheme in the learning process of “Kurikulum Merdeka” launched by The Ministryof Education, Culture, Research, and Technology of the Republic of Indonesia (2021). In thestructure of “Kurikulum Merdeka” in Vocational High School, English is included as one ofthe vocational subjects implying that the design of the lessons and the themes to bring up inthe learning process should be incorporated with the areas of expertise available in thecurriculum of Vocational High School. Hence, the meaningful lessons for the students arelikely to take place. By means of the analysis toward the learning achievement in “KurikulumMerdeka”, the article puts forward an application sample of English lesson as vocationalsubject in the concentration of Animation as one of the expertise areas of Arts and CreativeEconomics. In addition, the principles of arts integration lesson, differentiated learning, andsocial emotional instruction are included in the learning design as an attempt to interconnectthe pedagogical aspects in the lesson design.